EXPLORING THE RELATION OF ENVIRONMENTAL DISCLOSURE, ENVIRONMENTAL PERFORMANCE AND COMPANY CHARACTERISTICS IN INDONESIA; AN EMPIRICAL ANALYSIS - Dien Noviany Rahmatika (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study examines the effect of environmental disclosure on environmental performance, company characteristics, and type of industry. This type of research is descriptive quantitative with secondary data. The population is taken from the energy industry sector and the non-primary consumer goods industry sector listed on the IDX in 2016-2020. The sampling method used purposive sampling technique. The results of this study are environmental performance has an effect on environmental disclosure, company size has an effect on environmental disclosure, but profitability has no effect on environmental disclosure and the type of industry has no effect on environmental disclosure. Companies are expected to pay attention to the environmental disclosures in detail because obtaining high profits does not guarantee that the company is good in the community. Companies with small industries must disclose more environmental information in order to have a positive impact on society and the environment. Keywords: Environmental Performance and Environmental Disclosure, Profitability, Company Size, Type of Industry,